EXPLORING THE RELATIONSHIP BETWEEN WORKPLACE SPIRITUALITY AND ORGANIZATIONAL COMMITMENT AMONG HEALTHCARE PROFESSIONALS IN SAUDI ARABIA - Saleh Mohammed Alshammari, Reem Rkad Kalef Alshammari, Mashael Fahad Abu Salem, Maryam Rafa Alrashidi, Housing Department, Eid Mohammad Aljamily, Fahdah Murawwih Oshaywi Aldhafeeri, (Chelonian Research Foundation, 2022)
Workplace spirituality has garnered increasing attention in recent years as organizations seek to create more meaningful and fulfilling work environments. This study aims to explore the relationship between workplace spirituality and organizational commitment among healthcare professionals in Saudi Arabia. A cross-sectional survey design was employed, and data were collected from a sample of 350 healthcare professionals working in various settings across the country. The findings revealed a significant positive relationship between workplace spirituality and organizational commitment. Furthermore, the dimensions of workplace spirituality, namely meaningful work, sense of community, and alignment with organizational values, were found to be significant predictors of organizational commitment. The study highlights the importance of fostering workplace spirituality to enhance organizational commitment among healthcare professionals in Saudi Arabia. The implications of these findings for healthcare management and policy are discussed, along with recommendations for future research. Keywords: workplace spirituality, organizational commitment, healthcare professionals, Saudi Arabia